The effect of kinesio taping versus stretching techniques on muscle soreness, and flexibility during recovery from nordic hamstring exercise. Issue 1 (January 2017) - Ozmen, Tarik; Yagmur Gunes, Gokce; Dogan, Hanife; Ucar, Ilyas; Willems, Mark
Summary: The purpose of this study was to examine the effects of static stretching, proprioceptive neuromuscular facilitation (PNF) stretching, or kinesio taping (KT) on muscle soreness and flexibility during recovery from exercise. Sixty-five females were randomly assigned to four groups: PNF stretching (n = 15), static stretching (n = 16), KT (n = 17), and control (n = 17). All participants performed nordic hamstring exercise (5 sets of 8 repetitions). In all groups, hamstring flexibility at 24 h and 48 h was not changed from baseline (p > .05). The muscle soreness was measured higher at 48 h post-exercise compared with baseline in the control group (p = .04) and at 24 h post-exercise compared with baseline in the PNF group (p < .01). No significant differences were found for intervention groups compared with control group in all measurements (p > .05). The KT application and pre-exercise stretching have no contribute to flexibility at 24 h and 48 h after exercise, but may attenuate muscle soreness.